Analyses of Bloodmeal Hosts and Prevalence of Rickettsia parkeri in the Gulf Coast Tick Amblyomma maculatum (Acari: Ixodidae) From a Reconstructed Piedmont Prairie Ecosystem, North Carolina. Issue 4 (30th April 2022) - Johnson, Connie R; Ponnusamy, Loganathan; Richards, Allen L; Apperson, Charles S
Abstract: Host feeding patterns and the prevalence of infection with Rickettsia parkeri were determined for the primary vector, Amblyomma maculatum Koch as well as sympatric tick species A. americanum (Linnaeus) and Dermacentor variabilis (Say) collected from a reconstructed prairie in the Piedmont region of North Carolina during 2011 and 2012. The occurrence of R. parkeri among A. maculatum adults and nymphs was 36.9% (45/122) and 33.3% (2/6), respectively. Rickettsia parkeri was detected in a single male A. americanum 2.3% (1/43). A PCR-reverse line blot hybridization assay of a 12S rDNA fragment amplified from remnant larval and nymphal bloodmeals of host-seeking ticks was used to identify bloodmeal hosts. Of the tick samples tested, bloodmeal host identification was successful for 29.3% (12/41) of adult A. americanum and 39.2% (20/51) of adult D. variabilis . For A. maculatum, bloodmeal host identification was successful for 50% (61/122) of adults collected from vegetation and 100% (4/4) of nymphs removed from cotton rats ( Sigmodon hispidus Say and Ord). The cotton rat was the most common bloodmeal host with 59.0% (36/61) identified for adult A. maculatum . No statistically significant association was observed, however, between bloodmeal host and pathogen prevalence for any tick species. While the cotton rat was an important bloodmeal host for A. maculatum nymphs, this vertebrate did not appear to be the primary source of R. parkeri infection for A. maculatum .